2019
DOI: 10.1089/cap.2018.0139
|View full text |Cite
|
Sign up to set email alerts
|

Reported Adverse Drug Reactions in Children and Adolescents Treated with Antipsychotics

Abstract: Objectives: To characterize reported adverse drug reactions (ADRs) in children and adolescents treated with antipsychotics and determine differences in relative reporting frequency between genders, age classes, and reporter types. Methods: Individual case safety reports of children ages 1 -17 years in whom an antipsychotic drug was the suspected or interacting drug from the worldwide database, VigiBase, from 1968 until March 2017, were included. Reported ADRs were categorized based on the Standardized Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
2
23
0
4
Order By: Relevance
“…This study aims to provide a comprehensive overview of all ICSRs spontaneously reported to EV (one of the largest pharmacovigilance databases) in the pediatric population with a huge variety of psychiatric disorders treated with risperidone and aripiprazole, contributing to define their safety profiles in real-world settings. In line with recent pharmacoepidemiological studies evaluating the safety profile of SGAs in the young population, we found that the largest proportion of ICSRs was reported for boys, and the most frequently reported suspected antipsychotic drug was risperidone (19,20). These findings are consistent with previous evidence showing that male adolescents are more likely than females to be prescribed atypical antipsychotics and that risperidone is the SGA most commonly prescribed to the young population due to a wider spectrum of indicated uses (21).…”
Section: Discussionsupporting
confidence: 91%
“…This study aims to provide a comprehensive overview of all ICSRs spontaneously reported to EV (one of the largest pharmacovigilance databases) in the pediatric population with a huge variety of psychiatric disorders treated with risperidone and aripiprazole, contributing to define their safety profiles in real-world settings. In line with recent pharmacoepidemiological studies evaluating the safety profile of SGAs in the young population, we found that the largest proportion of ICSRs was reported for boys, and the most frequently reported suspected antipsychotic drug was risperidone (19,20). These findings are consistent with previous evidence showing that male adolescents are more likely than females to be prescribed atypical antipsychotics and that risperidone is the SGA most commonly prescribed to the young population due to a wider spectrum of indicated uses (21).…”
Section: Discussionsupporting
confidence: 91%
“…commented that, with the exception of drug companies, SRS are limited by their passivity because they are voluntary. 16 , 18 Montastruc et al ., 2015 suggested that notoriety bias (from safety alerts) accounted for the high numbers of reports with olanzapine and clozapine. 15 Minjon et al .…”
Section: Discussionmentioning
confidence: 99%
“… 15 Another recent observational cohort study by Ray et al ., showed that increased unexpected death was observed in children and youth using antipsychotics. 16 However, the results of this study were from hospitalised patients and lacked any information about the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well-documented that antipsychotic drugs frequently cause bothersome and even severe adverse drug reactions (ADRs), including cardiometabolic, endocrine, and extrapyramidal adverse effects (4,5). Examples of these adverse effects include weight gain, hypertension, gynecomastia, and parkinsonism (4)(5)(6). These ADRs can differ in frequency and relative impact in children compared to adults (7).…”
Section: Introductionmentioning
confidence: 99%